2021
DOI: 10.1021/acs.jctc.1c00513
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Ensemble Methods Can be Used to Accurately Predict Protein-Ligand Relative Binding Free Energies

Abstract: Alchemical free energy methods have become indispensable in computational drug discovery for their ability to calculate highly accurate estimates of protein-ligand affinities. Expanded ensemble (EE) methods, which involve single simulations visiting all of the alchemical intermediates, have some key advantages for alchemical free energy calculation. However, there have been relatively few examples published in the literature of using expanded ensemble simulations for free energies of protein-ligand binding. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…It is to be noted that FEP+ employs a different force field as compared to MELD-Bracket. Comparison, though not exactly apple-to-apple, is still advisable because of its wide acceptability and use for benchmark study. …”
Section: Resultsmentioning
confidence: 99%
“…It is to be noted that FEP+ employs a different force field as compared to MELD-Bracket. Comparison, though not exactly apple-to-apple, is still advisable because of its wide acceptability and use for benchmark study. …”
Section: Resultsmentioning
confidence: 99%
“…Absolute binding free energies computed using expanded-ensemble (EE) methods have been used previously in SAMPL challenges, 16,22 and our methods closely follow these efforts, with some innovations inspired by recent work. 42…”
Section: Methodsmentioning
confidence: 99%
“…Using this improved strategy, Zhang et al recently showed that EE methods can predict relative binding free energies of Tyk2 inhibitors to within a mean unsigned error (MUE) of 0.75 AE 0.12 kcal mol À1 . 42 The current SAMPL9 host-guest challenge represents the first time these improved protocols have been tested for predicting absolute binding free energies.…”
Section: (See Methods)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many enhanced sampling methods have been developed and applied to free energy simulations, such as different variants of replica exchange methods including replica exchange with solute tempering, grand canonical Monte Carlo, Gaussian accelerated molecular dynamics, weighted ensemble, metadynamics, orthogonal space tempering, and expanded ensemble. For more complete reviews, we refer the reader to refs . Despite significant advancements in enhanced sampling methods, sufficient sampling of systems with buried charges in many cases remains challenging.…”
Section: Introductionmentioning
confidence: 99%